Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Bulletin of the AAS 2021
DOI: 10.3847/25c2cfeb.cdb2753c
|View full text |Cite
|
Sign up to set email alerts
|

Enabling a New Generation of Outer Solar System Missions: Engineering Design Studies for Nuclear Electric Propulsion

Abstract: We discuss a nuclear electric propulsion (NEP) capability that would (1) enable a class of outer solar system missions that cannot be done with radioisotope power systems and (2) significantly enhance a range of other deep-space mission concepts. NASA plans to develop Kilopower technology for lunar surface power. Kilopower can also serve as a power source for a 10-kWe NEP system; therefore, we highlight 10-kWe NEP benefits to encourage the NASA Science Mission Directorate (SMD) to advocate (as a potential bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The most significant technological development would be the development of a nuclear electric propulsion system (NEP; cf. Casani et al, 2020), which would substantially decrease the cruise time to Pluto. Casani et al (2020) show that a 10-kilowatt-electric (kWe) NEP spacecraft can deliver 67% more payload with 2.4 years shorter flight time compared to the current radioisotope electric propulsion (REP) system.…”
Section: Introduction: the Case For Returning To The Kuiper Beltmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant technological development would be the development of a nuclear electric propulsion system (NEP; cf. Casani et al, 2020), which would substantially decrease the cruise time to Pluto. Casani et al (2020) show that a 10-kilowatt-electric (kWe) NEP spacecraft can deliver 67% more payload with 2.4 years shorter flight time compared to the current radioisotope electric propulsion (REP) system.…”
Section: Introduction: the Case For Returning To The Kuiper Beltmentioning
confidence: 99%
“…Casani et al, 2020), which would substantially decrease the cruise time to Pluto. Casani et al (2020) show that a 10-kilowatt-electric (kWe) NEP spacecraft can deliver 67% more payload with 2.4 years shorter flight time compared to the current radioisotope electric propulsion (REP) system. They also showed that a kWe system would enable greater than four times the data rate at Pluto compared with the REP option.…”
Section: Introduction: the Case For Returning To The Kuiper Beltmentioning
confidence: 99%